Chemical vapor transport synthesis of one-dimensional V2PS10 and its application in miniaturized UV sensors - Kang, Jinsu; Cho, Sooheon; Zhang, Xiaojie; Lee, Bom; Jeong, Byung Joo; Choi, Kyung Hwan; Jeon, Jiho; Lee, Sang Hoon; Park, Jae Hyuk; Kim, Sang Hyuk; Yu, Hak Ki; Choi, Jae Young (CrystEngComm, 2024)
This study investigates low-dimensional materials as a potential solution for the miniaturization of electronic devices, addressing the challenges posed by bulk materials. Our research successfully synthesized high-quality V2PS10 crystals using the chemical vapor transport method and confirmed their dispersibility in various solvents and their potential for mechanical exfoliation. In addition, a UV-sensing device was fabricated to evaluate its performance. In particular, at a wavelength of 254 nm, the fabricated V2PS10-based UV sensor exhibited a stable response current of 1.5 pA, demonstrating rapid response characteristics. These results underscore the importance of stable synthesis techniques and highlight the potential of V2PS10 as a one-dimensional UV-sensing material, thereby indicating its applicability to miniaturize electronic components.
Keywords: Bulk materials; Chemical Vapour Transport; Electronics devices; ITS applications; Low-dimensional materials; Miniaturisation; One-dimensional; Synthesised; UV sensor; UV-sensing